The relationship between thyroid hormones sensitivity and hyperhomocysteinemia: a cross-sectional study based on Chinese health check-up population - Gong, Rui; Xie, Jiao; Yu, Lixia; Ling, Yan; Wang, Shi; Min, Rui; Xu, Sanping (Frontiers in Endocrinology, 2025)
BackgroundIt is unclear if impaired thyroid hormone sensitivity interacts with homocysteine (Hcy), a known risk factor for cardiovascular diseases (CVD), despite the fact that it has been identified as a prevalent metabolic condition.We aimed to analyze the association between thyroid hormone sensitivity indices and homocysteine levels in a Chinese health check-up population.MethodsThyroid hormone sensitivity was assessed by the Thyroid Feedback Quantization Index (TFQI), the parameter TFQI (PTFQI), the TSH index (TSHI) and the thyrotropin thyroxine resistance index (TT4RI) and FT3/FT4 ratio. Linear regression analyses, logistic regression analyses and restricted cubic spline were used to investigate the relationship between thyroid hormone sensitivity and Hcy levels.ResultsThis study included 11144 medical examiners. Subjects with impaired thyroid hormone sensitivity had higher Hcy levels, according to the results (P < 0.001). Quartiles of TFQI, PTFQI, TSHI, and TT4RI were linked to Hcy levels, according to logistic regression analysis, and these associations persisted even after controlling for a number of risk factors. The odds ratio (95% CI) for Hyperhomocysteinemia (HHcy) in the highest quartile of TFQI was 1.294(1.114,1.504), for PTFQI was 1.293 (1.113, 1.503), and for TSHI was 1.222 (1.050, 1.422) (P < 0.001) after controlling for age, sex, body mass index, dyslipidemia, diabetes, and hypertension.ConclusionsA significant association between impaired thyroid hormone sensitivity and elevated Hcy levels exists in a Chinese population with normal thyroid function.